2016
DOI: 10.1108/ajb-04-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

The greening of organizational culture: revisited fifteen years later

Abstract: Purpose Organizations have viewed sustainability as a societal problem and unrelated to business. To recognize sustainability as an organizational issue requires companies to deal with the challenge of transforming into environmentally sustainable enterprises. This requires institutions to align mission statements with values. The purpose of this paper is to replicate previous research in sustainability and the cultural facets which impact the process. Design/methodology/approach A qualitative case study met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
4
26
1
1
Order By: Relevance
“…In this context it may be difficult for leaders and team members to introduce values reflective of green soft TM amid a firmly established hierarchical organisational culture (Jabbour, 2011;Roscoe et al, 2019). Ogbeibu et al (2018) argue that the organisational culture demonstrated within manufacturing organisations in Nigeria is firmly hierarchical, and studies (Auernhammer and Hall, 2014;Gupta, 2011;Naranjo-Valencia et al, 2016;Porter et al, 2016) lament that such organisational culture can stifle creativity, impair innovativeness, dampen job satisfaction, increase ineffective communication, and foster exclusion and alienation of talent. Congruently, studies suggest that this could provoke intention of organisational members to leave their organisation (Abdul et al, 2019;Deery and Jago, 2015).…”
Section: Jicmentioning
confidence: 99%
“…In this context it may be difficult for leaders and team members to introduce values reflective of green soft TM amid a firmly established hierarchical organisational culture (Jabbour, 2011;Roscoe et al, 2019). Ogbeibu et al (2018) argue that the organisational culture demonstrated within manufacturing organisations in Nigeria is firmly hierarchical, and studies (Auernhammer and Hall, 2014;Gupta, 2011;Naranjo-Valencia et al, 2016;Porter et al, 2016) lament that such organisational culture can stifle creativity, impair innovativeness, dampen job satisfaction, increase ineffective communication, and foster exclusion and alienation of talent. Congruently, studies suggest that this could provoke intention of organisational members to leave their organisation (Abdul et al, 2019;Deery and Jago, 2015).…”
Section: Jicmentioning
confidence: 99%
“…As public concern about environmental protection has been growing in recent years [ 1 , 2 ], many organizations and institutes have raised awareness of environmental practices by adapting their businesses to take charge of appropriate natural resource management and environmental management [ 3 , 4 ]. However, most of them neglect to guide employees to perform green behavior but concentrate only on the improvement of technical changes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to focus on how to create the flexibility of regulatory requirements on performance standards as well as regular SD monitoring and evaluation [29]. Furthermore, analysis by Porter et al [26] shows that the essential key success factors are public participation, zoning and institutional development. He stresses the importance of establishing related governmental organizations and management structures.…”
Section: Discussionmentioning
confidence: 99%